Distributions of Indo-Pacific lionfishes (Pterois spp.) in their native ranges: implications for the Atlantic invasion - Kulbicki, M.; Beets, J.; Chabanet, P.; Cure, K.; Darling, E.; Floeter, S.; Galzin, R.; Green, A.; Harmelin-Vivien, M.; Hixon, M.; Letourneur, Y.; De Loma, T.; et al. (Marine Ecology Progress, 2012)
Lionfish (Pterois volitans and P. miles) have become a major concern in the western Atlantic and Caribbean since their introduction in the 1980s. Invasive lionfish can reach very high population densities on coral reefs in their invaded range, yet there are few data from their native range in the Indo-Pacific for comparison. We compiled data on the geographical distribution and density of Indo-Pacific lionfishes in their native ranges from published and unpublished underwater visual censuses and field collections. We found that lionfish in their native Indo-Pacific range are unevenly distributed, with higher densities in the Indian Ocean than in the Pacific. Lionfish densities increase significantly with increasing latitude, and are significantly higher in continental areas than around islands. In the Indo-Pacific, lionfishes are found not only on reefs but also on soft bottoms and in nearshore habitats such as seagrass beds and mangroves, and near estuaries. Native lionfish can be found at depths greater than 75 m. Because lionfish can be cryptic and secretive, we estimate that only ~1/8 of Indo-Pacific lionfishes are detected during general underwater visual censuses. In the Pacific Ocean, the relative abundance of lionfish in the catch of reef-fish larvae is of the same order of magnitude as the relative abundance of adult lionfish within reef fish assemblages. Overall the observed densities of lionfishes in the Indo-Pacific are much lower (max. 26.3 fish ha–1) than the densities reported in their invaded Atlantic range (max. 400 fish ha–1). We found no effects of fishing or pollution on the densities of lionfishes.